Efficacy and safety of biologics in psoriatic arthritis: a systematic literature review and network meta-analysis. Issue 1 (23rd February 2020) - Ruyssen-Witrand, Adeline; Perry, Richard; Watkins, Clare; Braileanu, George; Kumar, Gayathri; Kiri, Sandeep; Nott, Debby; Liu-Leage, Soyi; Hartz, Susanne; Sapin, Christophe
Abstract : Background: Biologic disease-modifying antirheumatic drugs (bDMARDs) and targeted synthetic DMARDs are used in patients with psoriatic arthritis (PsA), but few studies directly compare their clinical efficacy. In such situations, network meta-analysis (NMA) can inform evidence-based decision-making. Objective: To evaluate the comparative efficacy and safety of approved bDMARDs in patients with PsA. Methods: Bayesian NMA was conducted to compare the clinical efficacy of bDMARDs at weeks 12‒16 in bDMARD-naïve patients with PsA in terms of American College of Rheumatology (ACR) criteria, Psoriatic Arthritis Response Criteria (PsARC) and Psoriasis Area and Severity Index (PASI). Safety end points were evaluated in the overall mixed population of bDMARD-naive and bDMARD-experienced patients. Results: For ACR, all treatments except abatacept were statistically superior to placebo. Infliximab was most effective, followed by golimumab and etanercept, which were statistically superior to most other treatments. Ixekizumab 80 mg every 2 weeks (Q2W) was statistically superior to abatacept subcutaneous, apremilast and both regimens of ustekinumab; similar findings were observed for ixekizumab 80 mg Q4W. For PsARC response, ixekizumab did not significantly differ from other therapies, except for golimumab, infliximab and etanercept, which were superior to most other agents including ixekizumab. For PASI response, infliximab was numerically most effective, but was not statistically superior to ixekizumab, which was the next best performing agent. Analysis of safety end points identified few differences between treatments. Conclusion: Our NMA confirms the efficacy and acceptable safety profile of bDMARDs in patients with active PsA. There were generally few statistically significant differences between most treatments.